Optimal Information Asymmetry, Control Environment, and Investment in Firm-Specific Human Capital - Brisley, Neil; Douglas, Alan V. (The Accounting Review, 2015)
ABSTRACT When future operations are expected to provide information rents, managers concerned with being replaced can entrench themselves with value-increasing firm-specific human capital (SHC). In motivating SHC investment, the firm trades off the incentive effects of an ex ante commitment to asymmetric information against the costs of compensation rents and private benefits. Firm value, therefore, is affected by (1) the accuracy with which the board observes and interprets information, and (2) the strength of the control environment restricting the manager's ability to benefit from concealing and diverting firm value. It is optimal to maintain a partially informed board to the mutual benefit of shareholders and managers, and for firms in a stricter control environment to maintain a more informed board. Due to the indirect effect on SHC, regulations that strengthen control adversely affect firm value unless the information and control environments are sufficiently biased toward managerial preferences. JEL Classifications: G30; G38; M12; M48.